Surface wettability analysis using a microdroplet: a numerical approach - Ganesh Meshram; Gloria Biswal; Ashish Khelkar (TESEA, Transactions on Energy Systems and Engineering Applications)
Analysis of hydrophobicity is essential for learning about the characteristics of molecules, surfaces, and materials that reject water. Using a two-dimensional (2D) pseudo-potential multiphase lattice Boltzmann approach with a D2Q9 model, this work examines the influence of solid-fluid interaction strength on wettability and hydrophobicity of smooth surfaces. To ascertain the contact angle and assess the accuracy of the numerical model, the study considers the equilibrium state of a water droplet on a smooth surface. In a 200×200 lattice unit domain, droplets having a radius of 60 lattice units are used to assess the hydrophobicity of smooth surfaces. According to the research, there is a large rise in the contact area between solid walls and water droplets when the solid-fluid interaction parameter is raised, which leads to a greater degree of hydrophobicity. By measuring the contact angle between the solid and fluid-vapor interface for different surfaces, it is observed that as G_ads becomes more negative, the contact angle decreases, indicating increased surface hydrophobicity, and the effect on droplet spreading is also highlighted in the research.